Comparisons of wave overtopping at coastal structures calculated with Amazon, COBRAS-UC and SPHysics - Neves, M. G. (2011)
The use of numerical models to calculate the mean overtopping discharges is, nowadays, more frequent in preliminary design of coastal structures, since they are more flexible than both empirical/semi-empirical and physical models and, once calibrated and validated, they can be applied reliably to a large range of alternative structure geometries and wave conditions. There are different models that can be used to calculate the mean overtopping discharges over a structure. The paper compares the output from three numerical models used to predict the mean overtopping discharges: AMAZON [1], based on solving the non-linear shallow-water equations; and two models based on Reynolds averaged Navier-Stokes equations, COBRAS-UC [2], a Eulerian model using the volume of fluid (VoF) method for surface capturing, and SPHysics [3], a Lagrangian model based on Smoothed Particle Hydrodynamics (SPH). The numerical results are also compared with experimental data obtained at the National Civil Engineering Laboratory (LNEC), Portugal, in the framework of the Composite Modelling of the Interactions between Beaches and Structures (CoMIBBs) project, a joint research activity of the HYDRALAB III European project [4]. The experimental work consists of wave propagation, with breaking, and wave overtopping of an impermeable seawall, a common coastal defense structure employed at the Portuguese coast. Results of free-surface elevation along the computational domain and of mean overtopping discharges are presented and discussed. Although the processes of wave generation used in the laboratory and in the models were different, the agreement in the free surface was reasonable: the wave period obtained with the models agreed very well with the data and the shape of the wave presented some minor differences to the physical model data, as well as the wave height. The results of mean overtopping discharges obtained with the three models agreed very well with the physical model results.